PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL PADA KEBIJAKAN DIVIDEN DENGAN FREE CASH FLOW SEBAGAI PEMODERASI - Widiari, Ni Nyoman Opi; Putra, I Wayan (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of managerial ownership and institutional ownership on dividend policy with free cash flow as a moderating variable. This research uses a panel data of all go public companies listed on the Indonesian Stock Exchange (IDX) 2011-2015. The sample choosen by purposive sampling method. There are 10 companies that meet the criteria as samples so that the research data totaling 50 observations. The analysis technique used in this study is Moderated Regression Analysis (MRA). The results of this study show that: 1) Ownership managerial significant negative effect on dividend policy. 2) Institutional ownership significant negative effect on dividend policy. 3) Free cash flow weaken the influence of managerial ownership on dividend policy. 4) Free cash flow weaken the influence of institutional ownership on dividend policy. Normal 0 false false false EN-GB X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} e-mail: o.sunz@yahoo.com telp: +62 89688602087 Normal 0 false false false EN-GB X-NONE X-NONE
Keywords: managerial ownership, institutional ownership, free cash flow, dividend policy.